2021
DOI: 10.3390/jcm10245881
|View full text |Cite
|
Sign up to set email alerts
|

Central Hemodynamic Adjustments during Post-Exercise Hypotension in Hypertensive Patients with Ischemic Heart Disease: Concurrent Circuit Exercise versus High-Intensity Interval Exercise. A Preliminary Study

Abstract: Concurrent aerobic plus resistance exercise (RAE) and high-intensity interval exercise (HIIE) are both effective at inducing post-exercise hypotension (PEH) in patients with hypertension. However, central hemodynamic changes associated with PEH in hypertensive subjects with underlying ischemic heart disease (IHD) have been poorly investigated. The study aim was to compare the acute effects produced by these two exercise modalities on left ventricular diastolic function and left atrial function. Twenty untraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…When compared with previous research, the increase in PALS and PACS after ECC-RE observed in the present study suggests that acute LA response to exercise could vary in relation to different exercise modalities and loads. This result is in agreement with another recent study, in which PALS and PACS increased, albeit not significantly, after a session of concurrent, aerobic plus resistance, exercise, while they were significantly decreased after a session of high-intensity interval exercise in subjects with hypertension and ischemic heart disease [ 36 ]. We observed that PALS increased in a similar manner after ECC-20 and ECC-50, while PACS increased to a greater extent after ECC-50 (+28.4%) than after ECC-20 (+18.1%).…”
Section: Discussionsupporting
confidence: 93%
“…When compared with previous research, the increase in PALS and PACS after ECC-RE observed in the present study suggests that acute LA response to exercise could vary in relation to different exercise modalities and loads. This result is in agreement with another recent study, in which PALS and PACS increased, albeit not significantly, after a session of concurrent, aerobic plus resistance, exercise, while they were significantly decreased after a session of high-intensity interval exercise in subjects with hypertension and ischemic heart disease [ 36 ]. We observed that PALS increased in a similar manner after ECC-20 and ECC-50, while PACS increased to a greater extent after ECC-50 (+28.4%) than after ECC-20 (+18.1%).…”
Section: Discussionsupporting
confidence: 93%
“…Marzolini et al [ 32 ] compared aerobic training alone versus aerobic plus resistance training, demonstrating that combined training was more effective on body composition, strength, and some indicators of cardiovascular fitness. However, most of the studies performed so far refer to patients with ischemic heart disease or heart failure [ 19 , 20 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intensity and duration have a significant effect on PEH. It has been shown that while a single session of aerobic plus resistance exercise (RAE) and high-intensity interval exercise (HIIE) can both bring about similar PEH in hypertensive patients with ischemic heart disease (IHD), RAE appears to have significantly less effect on diastolic and atrial functions, which makes it more suitable for reducing blood pressure in hypertensive patients with IHD [ 9 ]. Another method of inducing PEH is using sprint interval training (SIT), which has shown that the length of the interval between successive sprints and the age of the subjects can affect their post-exercise response.…”
mentioning
confidence: 99%